A review of the Drepanosticta carmichaeli-group, with the description of D. wildermuthi sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platystictidae) - Phan, Quoc Toan; Yokoi, Naoto; Makbun, Noppadon; Joshi, Shantanu; Subramanian, K.a.; Ngo, Quoc Phu; Dow, Rory A. (Zootaxa, 2021)
A modified and expanded definition of the Drepanosticta carmichaeli-group is given. This includes the species: D. annandalei Fraser, 1924, D. brownelli Tinkham, 1938, D. carmichaeli (Laidlaw, 1915), D. emtrai Dow, Kompier & Phan, 2018, D. hongkongensis Wilson, 1997, D. jurzitzai Hämäläinen, 1999, D. sumatrana Sasamoto & Karube, 2007, D. tenella Lieftinck, 1935, D. vietnamica Asahina, 1997 and D. wildermuthi sp. nov.). The species of the group are reviewed and in most cases illustrated, diagnostic notes are given wherever possible. Drepanosticta polychromatica Fraser, 1931 is considered to be a junior synonym of D. carmichaeli and variation in D. carmichaeli is discussed. Drepanosticta wildermuthi sp. nov. from the Central Highlands of Vietnam (holotype male from Bao Loc district, Lam Dong Province) is described. The female of D. jurzitzai Hämäläinen, 1999 is described for the first time. A key to the males of the Drepanosticta carmichaeli-group is provided.